1983
DOI: 10.1007/bf00845381
|View full text |Cite
|
Sign up to set email alerts
|

The effects of smoking and cigarette nicotine content on smokers' preparation and performance of a psychosocially stressful task

Abstract: This study examined the effects of tobacco smoking and cigarette nicotine content on four dimensions of emotional behavior (peripheral autonomic, electrocortical, cognitive, and overt motor) during both the preparation for and the performance of a psychosocially stressful task (extemporaneous speaking). Three groups of experienced smokers either did not smoke, smoked a low-nicotine cigarette, or smoked a high-nicotine cigarette while they were preparing to perform the speaking task. All subjects reported prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 15 publications
0
23
1
Order By: Relevance
“…As described in the original report (Fucito & Juliano, 2009), we were interested in whether exposure to an acute external stressor under minimal smoking deprivation conditions would affect immediate smoking motivation postexposure. A 1-hr deprivation requirement was selected to enhance ecological validity of the scenario as well as the effectiveness of the mood induction procedure, given that prior smoking laboratory studies have shown that smoking prior to a stressor (Fleming & Lombardo, 1987;Hatch, Bierner, & Fisher, 1983;Willner & Jones, 1996) has different effects on stress/negative affect than that after stress induction (Conklin & Perkins, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…As described in the original report (Fucito & Juliano, 2009), we were interested in whether exposure to an acute external stressor under minimal smoking deprivation conditions would affect immediate smoking motivation postexposure. A 1-hr deprivation requirement was selected to enhance ecological validity of the scenario as well as the effectiveness of the mood induction procedure, given that prior smoking laboratory studies have shown that smoking prior to a stressor (Fleming & Lombardo, 1987;Hatch, Bierner, & Fisher, 1983;Willner & Jones, 1996) has different effects on stress/negative affect than that after stress induction (Conklin & Perkins, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…This effect is attenuated but still present when subjects engage in social interac tions or are exposed to unpleasant, arousing stimuli [37,38], The stress of public speaking appears to be able to override any effects of smoking on HR [39].…”
Section: Hr Effects O F Smokingmentioning
confidence: 99%
“…43-47], Moreover, several studies have reported that smoking reduces anxiety [10,28,35,48.50], However, other studies have reported no effect of smok ing on anxiety [38,39,41,[51][52][53], Even within the same study, mixed results have been obtained [44,54], A possible explanation of negative anxiety results was proposed by Cutler and Barrios [51], who hypothesized that, if task difficulty is great enough, then any effects of smoking on anxiety are overshadowed by the reduction in anxiety that follows completion of the task. Such an expla nation may account for some of the negative findings, but cannot serve as a complete explanation.…”
Section: Effects O F Smoking On Anxietymentioning
confidence: 99%
“…Laboratory studies have also yielded inconsistent results. For example, some studies have manipulated affective states (e.g., induced NA) and then observed specific smoking behaviours such as rate, puff duration, number of puffs [5456]. These studies, however, have typically not found an association between smoking and NA, and when found they tend to be ephemeral [57], or occur inconsistently [58–61].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, only a few studies have modelled the relationship between smoking, stressor exposure, and NA simultaneously [54, 56], and we could not locate one published prospective study examining these relationships using a nationally representative sample. The studies conducted to date have found that the relationship between smoking and NA remains unchanged in the face of stressors.…”
Section: Introductionmentioning
confidence: 99%